2000
DOI: 10.1021/bi0014655
|View full text |Cite
|
Sign up to set email alerts
|

Hypermodified Nucleosides in the Anticodon of tRNALys Stabilize a Canonical U-Turn Structure,

Abstract: Modified nucleosides in the anticodon domain of Escherichia coli tRNA(Lys) are necessary for high-affinity codon recognition and reading frame maintenance. Human tRNA(Lys,3) is the specific primer for HIV-1 reverse transcriptase and also requires nucleoside modification for proper function. We now present NMR solution structures for the fully modified 17-nucleotide E. coli tRNA(Lys) anticodon stem-loop domain (ASL). NMR data were also collected for several partially modified ASLs, revealing the contributions e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 55 publications
3
82
1
Order By: Relevance
“…Comparing it with various hypomodified and unmodified analogs revealed opposing effects of the base modifications on ACNase reactivity. Correlating these data with the observed contributions of the base modifications to the ASL solution structure (12,14,15) leads us to suggest that ACNase prefers substrates where the anticodon nucleotides assume a stacked A-RNA conformation and where the base pairing interactions in the ASL stem are relatively destabilized. We also show that the PrrC D287H mutation renders human tRNA Lys3 relatively more reactive than the natural substrate.…”
Section: A Trnamentioning
confidence: 86%
See 2 more Smart Citations
“…Comparing it with various hypomodified and unmodified analogs revealed opposing effects of the base modifications on ACNase reactivity. Correlating these data with the observed contributions of the base modifications to the ASL solution structure (12,14,15) leads us to suggest that ACNase prefers substrates where the anticodon nucleotides assume a stacked A-RNA conformation and where the base pairing interactions in the ASL stem are relatively destabilized. We also show that the PrrC D287H mutation renders human tRNA Lys3 relatively more reactive than the natural substrate.…”
Section: A Trnamentioning
confidence: 86%
“…Comparing the NMR solution structures of a synthetic, fully modified tRNA Lys ASL and hypomodified counterparts has suggested that mnm 5 s 2 U34 and t 6 A37 rigidify the anticodon in a predominantly A-RNA stacked conformation. In addition, t 6 A37 modestly destabilizes the base pairing interactions of the ASL while mnm 5 s 2 U34 and ⌿39 counteract this effect (12). It is conceivable that these conformational effects influence ACNase reactivity.…”
Section: A Trnamentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen bond interaction between the ribose of U33 and the base 35 inferred from crystal structure analysis (see Table 1 Table 1) and the average (U33)O29 + + + H-C5(U35) angle ('1018) are compatible with the formation of a weak hydrogen bond (Wahl & Sundaralingam, 1997;Desiraju & Steiner, 1999)+ In this case, the (U33)O29-H bond points away from the C5-H group+ Multiple molecular dynamics (MMD) simulations of the yeast tRNA Asp anticodon hairpin, with explicit consideration of the solvent, support the existence of such a C-H + + + O interaction + From these MMD simulations, and from a MD simulation of the entire yeast tRNA Asp molecule in an aqueous environment , it has been observed that the (U33)O29-H group is located in the O39 conformational domain (Fig+ 3) and, therefore, points systematically away from the (U35)C5-H bond+ The average (U33)O29 + + + C5(C35) distance estimated from the molecular dynamics simulations is close to 3+5 Å+ Alternatively, from a recent NMR structure of the anticodon hairpin of Escherichia coli tRNA Lys,3 including all the modified nucleotides (Sundaram et al+, 2000), the average (U33)O29 + + + C5(U35) distance is calculated to be close to 5+0 (60+1) Å+ Although the (U33)O29 and (U35)C5 atoms are facing each other, these data invalidate the existence of a (U33)O29 + + + H-C5(U35) interaction and support instead the presence of a hydration pocket delimited by the (U33)O29 and the (U35)C5 atoms+ Yet, given the position of the hydrophilic atoms that delineate this putative binding site, a stable water molecule at this location is not really expected and is, indeed, not observed in the crystal structures+ Therefore, it seems reasonable to propose that the long (U33)O29 + + + C5(U35) distance may result from a local lack of NMR constraints that are particularly difficult to collect in loop regions+ Another example emphasizing the difficulty of deriving precise distances from NMR experiments in loop regions is given by the strong (U33)N3-H + + + OR-P(U36) hydrogen bond+ The average (U33)N3 + + + OR-P(U36) distance of 3+2 (60+4) Å derived from the NMR data is overestimated when compared to the distances of 2+8 and 2+6 Å extracted from the two recent high resolution crystal structures of yeast tRNA Phe , tr0001 and tr0002, respectively+ Thus, although NMR structural models lead to the very important conclusion that anticodon hairpins adopt folds in solution similar to those observed in tRNA crystal structures, they may, locally, lack precision for checking fine contacts+ When a cytosine is located at position 35, the (U33)O29-H group may establish a "stronger" hydrogen bond with the (C35)NH2 group, as was proposed earlier (Quigley & Rich, 1976), rather than with the (C35)C5-H group+ The recent tRNA Cys structure (extracted from the E. coli tRNA complex with EF-Tu, FIGURE 3. Conformational preferences for the (U33)O29-H group+ Left and right: Conformational wheel outlining the three favored O39, O49 and "Base" domains and the three forbidden H19, H29, and H49 domains (in gray) for the orientations of the 29-OH group of a ribose in a C39-endo conformation as deduced from MD simulations (Auffinger & Westhof, 1997)+ The C29-O29 axis is perpendicular to the plane of the page+ Left: With a purine at position 35, the (U33)O29-H bond (bold arrow) is located in the "base" domain with an average H29-C29-O29-H dihedral angle close to 3238 as deduced from structural considerations involving the position of the (R35)N7 atom+ R...…”
Section: Introductionmentioning
confidence: 92%
“…This mark is also enriched at alternatively spliced introns and over long exons (Dominissini et al, 2012), suggesting a role in modulating splicing. Moreover, Y modifications in tRNAs stabilize secondary structures (Sundaram et al, 2000;Kierzek et al, 2014) and may do the same in mRNAs in which they are incorporated (Carlile et al, 2014;Schwartz et al, 2014b). Similarly, as tRNA modifications are known to direct cleavage of internally transcribed spacers, mRNA modifications could likewise direct transcript cleavage and subsequent turnover (Hughes and Ares, 1991;Kiss-László et al, 1996).…”
Section: Introductionmentioning
confidence: 99%